GANGGUAN BERBAHASA ARAB BAGI ANAK AUTIS DAN AL-QUR`AN SEBAGAI TERAPI PENGOBATAN (Studi kasus di Sekolah Taruna Al-Qur`an Yogyakarta) - Ferawati ` Ferawati (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
Language disorder as a symtom of autism has been found in many autistic children. However, one to another has different characteristics of language disorder. This study aims to find out how children with autism have an Arabic disorder and how the process of al-Quran therapy as a media of treatment.The method used in this research is qualitative approach with analytic descriptive research type. The results obtained from this study is in the case of Arabic not all types of language disorders experienced by children with autism and disorders experienced differently from one another. In practice, al-Quran therapy performed 6 days ie Monday to Saturday, in a day of therapy is done twice that after praying dluha and duhur prayer except Saturday is only done after solat duhur only. Al-Qur'an therapy can be understood as a phenomenon that seeks to provide an alternative treatment in people with autism.